The “Trinity” smart hospital construction policy promotes the development of hospitals and health management in China - Zhang, Guang-Wei; Gong, Mengchun; Li, Hui-Jun; Wang, Shuang; Gong, Da-Xin (Frontiers in Public Health, 2023)
Recently, in order to comprehensively promote the development of medical institutions and solve the nationwide problems in the healthcare fields, the government of China developed an innovative national policy of “Trinity” smart hospital construction, which includes “smart medicine,” “smart services,” and “smart management”. The prototype of the evaluation system has been established, and a large number of construction achievements have emerged in many hospitals. In this article, the summary of this field was performed to provide a reference for medical workers, managers of hospitals, and policymakers.